Divine Image - Middlemas, Jill Anne (Forschungen Zum Alten Testament 2. Reihe, 2015)
Cover -- Acknowledgements -- Table of Contents -- Chapter 1: Aniconism and the Imago Dei -- Origins of Aniconism -- The Prophetic Contribution to the Aniconism Debate -- Aniconism and Anthropomorphism -- The Structure of the Book -- Chapter 2: Idol Polemics -- The Polemic Against the Idols Passages -- PAI Passages in Second Isaiah -- PAI Passages in Jeremiah and Habakkuk -- Summary of Aniconic Strategies in the PAI Passages -- Idol Polemics -- Terms of Divinity -- Demotion and Defamation -- Identification with Human Construction and Materials -- Programmatic Aniconism and the Destruction of Idols -- Summary of Aniconic Strategies in the General Idol Polemics -- Deliberate Misrepresentation -- Biblical Evidence of Deliberate Distortion -- Enlivening the Cult Statue and Biblical Distortion -- Conclusions -- Chapter 3: Iconoclasm: Aniconism & the Image of Yahweh -- Distancing the Divine from Concrete Forms -- Bull Iconography of the Northern Kingdom -- Monarch Iconography of the Southern Kingdom -- The Cherubim Throne -- The Ark -- Distancing the Divine from Human Figuration -- Formless Iconography and the Second Temple -- Conclusions -- Chapter 4: Incomparability, Metaphor, and Multiple Imaging -- Divine Incomparability -- Divine Incomparability and the Old Testament Prophets -- Divine Incomparability in the Ancient Near East -- Metaphor and Multiple Imaging -- Modeling Similes -- Divine Comparability in Second Isaiah -- Divine Comparability in Ezekiel -- Divine Comparability in Hosea -- Multiple Imaging in the Prophetic Literature -- Conclusions -- Chapter 5: The Imago Dei and Prophetic Aniconism -- Priestly Divine Image Passages -- Second Isaiah Divine Image Passages -- Ezekiel Divine Images Passages -- Priestly and Prophetic Conceptions of the Imago Dei -- Conclusions -- Chapter 6: Conclusions -- Bibliography -- Sources